The Effect of Health Promotion Through Animation Video On Knowledge About Prevention Of Sexual Violence Children In Bulukumba District (Lembaga Penelitian dan Pengabdian Masyarakat Stikes Panrita Husada Bulukumba, 2024)
Background: The rise of news in the mass media regarding sexual violence against children is enough to make people surprised. This phenomenon is increasingly happening and becoming global in almost various countries. This increase is not only in terms of quantity but also in terms of quality, and what is even more tragic is that most of the perpetrators are from the family or surrounding environment, including in their own homes, schools, educational institutions, and the child's social environment. Efforts that can be made to prevent and protect children from the threat of sexual violence, one of which is by providing education or health promotion about preventing sexual violence in children. media that can be used can be through auditive, visual and audiovisual media.Research objective: To determine the effect of health promotion through the media of mass animation videos on increasing children's knowledge about preventing sexual violence at SDN 171 Loka BulukumbaResearch Method: Pre-experimental with One Group Pretest Posttest Design. The sample size is 43 respondents, with the sampling technique that is probability sampling using the sampling technique that is Simple random sampling.Research Results: Obtained knowledge value Pretest increased during the posttest. The results of the Wilcoxon test show that the level of knowledge about preventing sexual violence in children has a P-Value = 0.000 so that the P-Value < Ha (0.05)Conclusions & Suggestions: There is an influence of animated video media on children's knowledge about preventing sexual violence at SDN 171 Loka Bulukumba. Suggestions from this study are that future researchers will intervene not just once so that it is more effective in increasing children's knowledge.